PENGARUH KINERJA ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) TERHADAP INOVASI HIJAU PERUSAHAAN DENGAN MODERASI TINGKAT KEPATUHAN PERUSAHAAN TERHADAP REGULASI PEMERINTAH DAN KOMITE ESG (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2021 - 2024) - Nabila Nur Afiifah; Dwi Ratmono (Diponegoro Journal of Accounting, 2026)
This study examines the effect of Environmental, Social, and Governance (ESG) performance on corporate green innovation and investigates the moderating roles of government regulation compliance and ESG committees in manufacturing companies listed on the Indonesia Stock Exchange during 2021–2024. Using a quantitative approach and purposive sampling, data were collected from annual reports, sustainability reports, and financial reports. Green innovation was measured using Green Product Innovation (GPI) and Green Process Innovation (GPR). The data were analyzed using panel data regression and Moderated Regression Analysis (MRA). The results show that ESG performance positively and significantly affects corporate green innovation, indicating that better ESG practices encourage sustainability-oriented innovation. Furthermore, compliance with government regulations negatively moderates the relationship between ESG performance and green innovation. However, ESG committees do not significantly moderate the relationship. These findings suggest that ESG implementation plays an important role in promoting green innovation, while the effectiveness of regulatory compliance and ESG committees in strengthening this relationship remains limited.